Families, Taxes and the Welfare System - Nicole B. Simpson (Institute for the Study of Labor (IZA), 2013)
In this paper, I will describe in detail both the Earned Income Tax Credit and the Child Tax Credit in the U.S., including their origins, their structure, and the effects they have on the labor market and family formation. I will then discuss the macroeconomic implications of U.S. welfare reform, and then conclude by analyzing the effectiveness of the U.S. safety net (broadly defined) during the Great Recession of 2007-2008.
Keywords: D1; H24; H53; 330; taxes; welfare; families; EITC; child tax credit; TANF